Impact of Nutrient-Gene-Interaction on Periodontal DiseasesAn Over View - Razia Haidrus1 , Sangeeta U Nayak2 , Deepa G Kamath3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The key role to maintain equilibrium between microbial challenge and host response is played by nutrition,which is also important in various chronic diseases like cardiovascular disease, type 2 diabetes & rheumatoidarthritis. An individual’s baseline inflammatory position is influenced by macronutrients & micronutrientswhich modulate pro inflammatory and anti-inflammatory cascades. The aim of this review is to give aninsight on mechanism of action of various macronutrients, micronutrients and some of the trace elementswith their positive effects in resolution of various chronic diseases such as diabetes, cardiovascular, cancerand periodontal diseases. Thus dietary changes can be associated with genetic composition, this in turn maybe due to changes in individual response. This highlights the significance of unravelling the role of nutrientgene interaction in progression of chronic diseases. Periodontitis is linked to a number of chronic systemicdiseases which emphasize the significance of effective periodontal disease management for tooth retentionas well as for overall health.